SIKULON E-LEARNING ANALYSIS: POLICY DETERMINATION ANALYSIS OF E-LEARNING IMPLEMENTATION AT IAIN SURAKARTA - Mujtahid, Mujtahid; Supriyatno, Triyo; Sutiah, Sutiah; Irawan, Andik Rony; Fatahillah, Faisal Rois (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
It has become an important requirement of every university to formulate and implement policies related to e-learning. IAIN Surakarta in this case is still new in terms of implementing e-learning. Even the carrying capacity ranging from policies, infrastructure, and so on is still not fully available. This study aims to analyze the process of policy formulation on e-learning at IAIN Surakarta. This study uses a descriptive qualitative approach. The qualitative approach is more emphasized the process of extracting data from primary sources, namely policymakers and policy documents that have been formulated and implemented. This research was conducted at the IAIN Surakarta campus. The data collection technique used data taken from subjects and informants, as well as document data related to e-learning policies and implementation. To test the validity of the data, this study used source triangulation and Focused Group Discussion (FGD). Data analysis uses an interactive model from Miles and Huberman. This study found that the formulation of e-learning implementation policies at IAIN Surakarta was carried out with a pragmatic and top-down situational approach. The main considerations used in policy formulation are health and safety aspects, in addition to other considerations, namely economic technology, psychology, and experience. The timing of the formulation of e-learning-based learning implementation policies found the right momentum with the presence of the Covid-19 pandemic. While the policy targets for implementing e-learning include all parties including academic managers at the Tarbiyah Faculty level, PAI study programs, related units, lecturers, and students.